Peran Media Sosial Instagram dalam Mendukung Program Komunikasi Pemasaran Samakta Guest House - Nantingkaseh, Alfonso Harrison (School of Communication - Atma Jaya Catholic University of Indonesia, 2020)
The development of internet-based communication technology has had a major impact on communication functions, one of which is in the marketing communication function. Social media becomes a very reliable technology feature for business entities such as companies in carrying out marketing communications and achieving marketing objectives, namely sales and profits. Samakta Guest House as one of the lodging accommodation business practitioners began to adopt social media in order to support its marketing communication program. Through this research, the researcher intends to observe the understanding and basic technical skills of the Samakta Guest House’s marcomm officer regarding the concept of social media-based marketing communication. This study will use the qualitative indepth interview and observation method to understand the Samakta Gueset House marketing communication management phenomena, and then using literature study based on the concept of integrated marketing communication, new media in particularly social media Instagram (IG). The findings of this research are expected to contribute to the understanding of Samakta Guest House Management regarding the skills of utilizing social media, specifically Instagram. Thus, from their understanding of the concept of marketing communication, in the future the management will be increasingly capable to manage various social media contents to support the achievement of sales profits for the company.